FS - Reynolds, Eric 1971- (Fantagraphics Books Inc., 2019)
A collection of the Black Hole cartoonist’s secret, self-published sketchbooks and zines. Since 2000, master cartoonist Charles Burns has been self-publishing a secret, handmade sketchbook zine titled Free S**t, exclusively for friends and VIPs. For the first time, Burns has compiled all twenty-five issues into a single pocket-sized volume for all of his fans to enjoy. Featuring finished drawings, rough sketches, process pieces, and more, the book is a revealing behind-the-scenes look at how characters and motifs in acclaimed works like Black Hole and Last Look have evolved.
ISBN im Impressum falsch angegeben
"Free Shit. This is a collection of the first twenty-two issues"
First printing: September 2019
Keywords: Burns, Charles -- 1955-; Comic